2022
DOI: 10.1002/acr2.11500
|View full text |Cite
|
Sign up to set email alerts
|

Preferences and Insights for Participation in a Rheumatoid Arthritis Clinical Prevention Trial: A Mixed‐Methods Study

Abstract: Objective In rheumatoid arthritis (RA), anti–citrullinated protein antibodies (ACPA) can be elevated prior to inflammatory arthritis (IA). The potential to intervene in people with ACPA positivity underpins the development of prevention trials in RA. The Research Participation Influences Study examined factors influencing the decisions of individuals who are ACPA(+) to participate in a prevention trial using qualitative and quantitative methods. Methods Individuals with ACPA positivity without IA were provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recent research indeed showed differences between enrollees and nonenrollees in a trial on, for example, concerns about medication effects. 15 Therefore, attitudes among trial participants in the current study, definitely need to be validated in other CSA patients. As also mentioned in figure 1 of the publication on the results of the TREAT EARLIER trial, 89 (23%) of the CSA patients who were eligible for the trial did not want to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indeed showed differences between enrollees and nonenrollees in a trial on, for example, concerns about medication effects. 15 Therefore, attitudes among trial participants in the current study, definitely need to be validated in other CSA patients. As also mentioned in figure 1 of the publication on the results of the TREAT EARLIER trial, 89 (23%) of the CSA patients who were eligible for the trial did not want to participate.…”
Section: Discussionmentioning
confidence: 99%